Validation of Self-application-based Malnutrition and Limited Mobility Screening Tools Compared with Standard Diagnostic Tools in Older Adults - Tanaviboon, Panvadee; Muangpaisan, Weerasak; Jongsawadipatana, Angkana; Siritipakorn, Pitiporn; Intalapaporn, Somboon (Siriraj Medical Journal, 2025)
Objective: To validate application screening tools against face-to-face standard tools (the Mini Nutritional Assessment (MNA) and Short Physical Performance Battery test (SPPB)) in older adults. Materials and Methods: A mobile or tablet application was developed based on user interfaces and experiences. Outpatients aged 60 years and over were tested with this tool. We used 2 questions from the WHO-ICOPE algorithm and 3 questions from the STEADI algorithm to screen for at-risk malnutrition and limited mobility, respectively. The MNA and SPPB were used to detect malnutrition and limited mobility, respectively, to test their validity. Results: The study involved 187 participants, 16% of whom were diagnosed with at-risk malnutrition by the MNA and 18.7% of whom had limited mobility according to the SPPB. The sensitivity and specificity of the malnutrition application tool were 66.6% and 96.1%, respectively. When BMI < 18.5 was combined in the application, the sensitivity and specificity were 90% and 91%, respectively. For limited mobility, the sensitivity and specificity of the application were 94.2% and 76.3%, respectively. The majority of participants rated the application for easy understanding as «excellent» (65%) and rated their confidence in their ability to use the application by themselves as “excellent” (70%). Conclusion: The application is an age-friendly, time-saving tool that can be used when face-to-face screening is vdifficult with good validity.